Translation of a Leaderless Reporter Is Robust During Exponential Growth and Well Sustained During Stress Conditions in Mycobacterium tuberculosis - Grabowska, Anna D.; Andreu, Nuria; Cortes, Teresa (Frontiers in Microbiology, 2021)
Mycobacterium tuberculosis expresses a large number of leaderless mRNA transcripts; these lack the 5′ leader region, which usually contains the Shine–Dalgarno sequence required for translation initiation in bacteria. In M. tuberculosis, transcripts encoding proteins like toxin–antitoxin systems are predominantly leaderless and the overall ratio of leaderless to Shine–Dalgarno transcripts significantly increases during growth arrest, suggesting that leaderless translation might be important during persistence in the host. However, whether these two types of transcripts are translated with differing efficiencies during optimal growth conditions and during stress conditions that induce growth arrest, is unclear. Here, we have used the desA1 (Rv0824c) and desA2 (Rv1094) gene pair as representative for Shine–Dalgarno and leaderless transcripts in M. tuberculosis respectively; and used them to construct bioluminescent reporter strains. We detect robust leaderless translation during exponential in vitro growth, and we show that leaderless translation is more stable than Shine–Dalgarno translation during adaptation to stress conditions. These changes are independent from transcription, as transcription levels did not significantly change following quantitative real-time PCR analysis. Upon entrance into nutrient starvation and after nitric oxide exposure, leaderless translation is significantly less affected by the stress than Shine–Dalgarno translation. Similarly, during the early stages of infection of macrophages, the levels of leaderless translation are transiently more stable than those of Shine–Dalgarno translation. These results suggest that leaderless translation may offer an advantage in the physiology of M. tuberculosis. Identification of the molecular mechanisms underlying this translational regulation may provide insights into persistent infection.